Biocompatible bright orange emissive carbon dots: Multifunctional nanoprobes for highly specific sensing toxic Cr(VI) ions and mitochondrial targeting cancer cell imaging - Ramar Rajamanikandan; D.S. Prabakaran; Kandasamy Sasikumar; Joo Seon Seok; Gyeongchan Lee; Heongkyu Ju (Talanta Open)
Although several luminescent-based nanostructured materials are used as cellular imaging probes, creating a biocompatible subcellular imaging probe can be challenging. Instantaneously, it is crucial and urgently needed for certain fluorescent nanoprobes to identify possibly harmful heavy metal ions. We present a straightforward one-pot preparation of bright orange emissive (quantum yield approximately 16 %) Nitrogen/Sulfur co-doped carbon dots (N/S CDs) from citric acid and methylene blue as raw materials that will serve as a specific Cr(VI) ions sensor and an effective mitochondrial labeling in cancer cells. They had several benefits including low ecological impact, facile synthesis, good water solubility, photostability, and high stability. We found that N/S CDs photoluminescence (PL) could be reduced when Cr(VI) ions were present near them, and the PL reduction occurred highly sensitively to the presence of Cr(VI) compared to other metal ions including Cr(III) ions. This specific reduction of PL was due to the non-fluorescent complex formation through the inner filter effect (IFE). The established fluorescence-based sensing technique could serve for Cr(VI) ion quantification with exceptional sensing efficiency in the wide linear range of 7 to 70 μM (R2 = 0.9873), with the limit of detection of 53.5 nM. It was also revealed that the current fluorescent probe could be encouragingly utilized to quantify the concentration of Cr(VI) ions in various water specimens such as tap water. In addition, they were shown to function as a mitochondria-targeting nanoprobe in human cancer cells (ME 180 cells and Hela cells) for cell imaging. Concludingly, it was envisioned that these fluorescent nanoprobes could find a use in real-time monitoring of Cr(VI) ions in water-based ecosystems with ultrahigh sensitivity and cell image tracking via mitochondria labeling as biocompatible nanoprobes.